Investigation of Frequency Split Phenomenon of Rolling Tire Vibration Property Using a New Naming Convention - Xudong Yu; Chendi Zhu; Yan Zeng; Haibo Huang (Shock and Vibration)
Tire as the only contact part between automobiles and road surface plays an important role in noise, vibration, and harshness (NVH) performance of automobiles. Free vibration characteristics of a nonrotating tire have been extensively studied, but the vibration behaviour of a rolling tire still needs further investigation, especially the high-order vibration higher than 300 Hz. Since the modal characteristics are highly dependent on the stresses induced from external loading and rolling speed, a finite element (FE) model was established for investigating rolling tire natural frequencies and mode shapes including high-order vibration. The effects of the vertical load and rolling speed are incorporated in the analysis through an explicit dynamic simulation to determine the stress state throughout the tire at instants when the modal characteristics are desired. The contact features between the tire and road obtained from the numerical FE method are verified by a vertical loading test experimentally, and then the FE model of a free tire in a frequency range of 0–500 Hz is validated by the hammering test. A great agreement between the FE model and experimental results of tire is found. A new naming convention combining wave numbers and travelling wave direction is developed to identify and categorize modes of the static and rolling tires, respectively, based on travelling wave vibration theory. The influences of vertical load and rolling speed on tire natural frequencies are examined by the FE model, and the results show that the mode frequencies of rolling tire diverged to two different frequencies with one being lower and the other being higher than the corresponding frequency of static tire alone. This study provides deeper understanding of complex dynamic properties, which are beneficial to designing and optimizing of tire-vehicle systems and identification of the critical rolling speeds.